Qualities of teachers of primary school in the process of vocational training - Ainur Taurbekova, Kalibek Ybyraimzhanov, Symbat Chunkenova , Marianna Sydykbekova, Nurlan Abishev, (Opción, 2019)
The study aims to investigate the personal qualities of future teachers of primary school in the process of vocational training via a complex, multi-component pedagogical method. As a result, psychological training should combine organizational, purely functional aspects of the development of properties, qualities, the potential of the student as a future specialist with the formation of their stable personal motivation of educational activity. In conclusion, the analysis of experimental work, in particular, the forming experiment, allowed to identify and experimentally justify the pedagogical conditions of effective vocational training of the future teacher in the process of the student group.